Social Norms and Gendered Occupational Choices of Men and Women: Time to Turn the Tide? - Patricia Palffy; Patrick Lehnert; Uschi Backes-Gellner (Institute of Labor Economics (IZA), 2022)
We analyze the relationship between social gender norms and adolescents' occupational choices by combining regional votes on constitutional amendments on gender equality with job application data from a large job board for apprenticeships. Results show that adolescent males in regions with stronger traditional social gender norms are more likely to apply for typically male occupations. This finding does not hold for females, suggesting that incentivizing men to break the norms and choose gender-atypical occupations (e.g., in healthcare) can be even more effective in accelerating advancement toward gender equality in the labor market than incentivizing women to choose STEM occupations.
Keywords: J24; J16; I24; M59; 330; occupational gender segregation; social norms; occupational choice